THE EFFECT OF TRAINING AND EDUCATION AND WORK MOTIVATION ON THE COMPETENCE AND PERFORMANCE OF SATPOL PP AND DAMKAR EMPLOYEES OF TANAH LAUT DISTRICT - Amrullah, Amrullah; Nurus Sjamsi; Melania, Melania (Jurnal Ekonomi, 2023)
The purpose of this study is to determine and analyze: 1) the influence of training on employee competence 2) the influence of work motivation on employee competence 3). the influence of training on employee performance 4). the influence of work motivation on employee performance 5). the influence of competence on employee performance 6). the influence of training on employee performance through competence 7) the influence of work motivation on employee performance through competence. The population in this study were all Satpol PP and Damkar employees totaling 150 employees. The sampling technique in this study used purposive sampling. The sample in this study was 37 employees. Data were analyzed using path analysis with the help of smart PLS SEM (Partial Least Square-Structural Equation Modeling) software. The results of the study found that: 1) Training has an effect on employee competence. 2) Work motivation has an effect on employee competence. 3) Training has an effect on employee performance. 4) Work motivation has an effect on employee performance. 5) Competence has an effect on employee performance. 6) Training has an effect on employee performance through competence. 7) Work motivation has an effect on employee performance through competence.